Non-appendicitis Diagnoses in Patients Operated Due to Acute Appendicitis - Dincer, Mursit; Degerli, Mahmut Said; Gur, Huda Umit; Citlak, Gamze (Galenos Yayincilik, 2019)
Aim: The aim of the present study was to evaluate patients who were operated due to acute appendicitis and who were later determined to have non-appendicitis pathologies. Methods: The demographic characteristics, histopathological results existence of perforation, complications and the length of hospital stay were recorded. The data of the patients who were determined to have histopathological results other than acute appendicitis were analyzed. Results: A total of 2112 patients, who underwent surgery due to acute appendicitis were included in the study. Sixty-seven-pointfive percent of the patients were male (n=1426). The average age was 33.6 +/- 12.9 years and the median age was 30 (19-90) years. The patients were divided into two groups as those under the age of 30 (Group 1) and above the age of 30 (Group 2). No significant differences were detected between the two groups in terms of histopathological diagnoses, perforation, complication and length of hospital stay. Normal appendix was found in 0.6% and non-appendicitis pathologies in 1.5% (n=33) of patients. Conclusion: Despite advances in radiological imaging a significant number of malignancies and other diagnoses might be detected in patients operated for acute appendicitis; therefore, histopathological analysis of appendicectomy specimens is of great importance.
Akut apandisit nedeniyle ameliyat edilen hastalarda apandisit dışı tanılar
Keywords: Acute appendicitis; histopathology; surgery